The narrative as a weapon: the conceptual challenges of post-truth in the 21st century - Lagos, Alejandro Gabriel (2025)
This article explores the phenomenon of disinformation, emphasizing the 2016 Colombian case (Peace Plebiscite) and the Chilean case of 2022 (Constitutional Convention). The premise is that these articulations were deployed for specific political purposes, within a context of heightened narratives and positions framed by a post-truth regime, understood as an intensification of emotionally charged argumentation. Furthermore, the infodemics of 2016 in Colombia and 2022 in Chile arose under specific enabling conditions, ranging from enemy-making strategies and current modes of production to techno-scientific advances and new understandings and practices of warfare. It is argued that only an interdisciplinary strategy can understand and stabilize such phenomena conceptually and categorically.